2022
DOI: 10.31602/ann.v9i1.6498
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Kasus Jaringan Lunak Rongga Mulut Di Kota Banjarmasin Tahun 2017 – 2020

Abstract: Penyakit jaringan lunak rongga mulut berkembang dengan angka kejadian yang bervariasi, yaitu 2,5 hingga 58 persen di berbagai jenis populasi. Kejadian penyakit rongga mulut meliputi 58% dari populasi lansia dan 34,8% pada populasi anak-anak. Penelitian ini bertujuan untuk mengetahui gambaran penyakit jaringan lunak rongga mulut di Kota Banjarmasin tahun 2017-2020. Jenis Penelitian ini adalah penelitian kuantitatif dengan analisis data deskriptif. Variabel dalam penelitian ini adalah penyakit jaringan lunak ron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…The percentage of periodontal disease was 81.22% in 2017, 73.89% in 2018, 81.33% in 2019, and 71.54% in 2020. 13 The result of this study is also supported by the data from the Central Bureau of Statistics (BPS) of Hulu Sungai Selatan Regency which showed that periodontal disease was one of the 10 most common diseases in one of the community health center (Puskesmas) in Daha Selatan Subdistrict, namely Puskesmas Bayanan, with a total of 739 cases in 2020. 14 Periodontal disease is affected by various factors, one of them is a predisposing factor, namely behavior.…”
Section: Discussionsupporting
confidence: 73%
“…The percentage of periodontal disease was 81.22% in 2017, 73.89% in 2018, 81.33% in 2019, and 71.54% in 2020. 13 The result of this study is also supported by the data from the Central Bureau of Statistics (BPS) of Hulu Sungai Selatan Regency which showed that periodontal disease was one of the 10 most common diseases in one of the community health center (Puskesmas) in Daha Selatan Subdistrict, namely Puskesmas Bayanan, with a total of 739 cases in 2020. 14 Periodontal disease is affected by various factors, one of them is a predisposing factor, namely behavior.…”
Section: Discussionsupporting
confidence: 73%